If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10x + -2(1) = 2 Multiply -2 * 1 10x + -2 = 2 Reorder the terms: -2 + 10x = 2 Solving -2 + 10x = 2 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 10x = 2 + 2 Combine like terms: -2 + 2 = 0 0 + 10x = 2 + 2 10x = 2 + 2 Combine like terms: 2 + 2 = 4 10x = 4 Divide each side by '10'. x = 0.4 Simplifying x = 0.4
| 20-2a+4a+4a+7=48 | | 5x+-4=8+2x | | (4x+2)-(3x-6)= | | -5(.2+.2y)=-2 | | -8(5+b)-1=-89 | | 124=7x+3(x+8) | | 2(x+8)=9x-6 | | 6x-2y=48 | | (2+x)(x-3)=24 | | 5xn-3=12 | | 7x-22=6x-22 | | 10x-2y=2 | | 20-4a+4a+4a+7=48 | | -6(1+8k)=-102 | | 9.6=1.6 | | 6b+4=12 | | 8y-3y=75 | | (7y+6)-(5+6y)=5 | | (3)(2x)(x)=36 | | 3x-2(5(6)+14)=-14 | | 4.1x-4=3.1x | | 3x-9(-4)=36 | | 6(-3x+6)=-180 | | 3x-2(5(6)+14)= | | -12-3y-3y=12 | | x^2+10=18x-12 | | 3(x+6)+8=5x-6 | | (35)=3x+2 | | 3t=37 | | B=r+50 | | 6x-5+4x-4=x | | 2x+67=-8x+107 |